Design and Methodology of The Irish Longitudinal Study on Ageing. (10th May 2013) - Whelan, Brendan J.; Savva, George M.
Abstract : Objectives: To provide comprehensive data on older people in Ireland and new insights into the causal processes underlying the aging transformation. Design: The Irish Longitudinal Study on Ageing (TILDA) is a population‐representative prospective cohort study with baseline assessment conducted between October 2009 and Febraury 2011 and follow‐up waves planned every 2 years. Participants were sampled in geographic clusters, with each member of the Irish population aged 50 and older having an equal probability of being invited to participate in the study. Setting: Community‐living population of the Republic of Ireland aged 50 and older. Participants: Eight thousand one hundred seventy‐five participants aged 50 and older at time of interview participated in the study, along with 329 spouses or partners younger than 50. Measurements: The Irish Longitudinal Study on Ageing includes detailed assessments of the mental and physical health and social and financial circumstances of participants, which are assessed in a home interview, a self‐completion questionnaire, and a detailed health assessment that takes place at a dedicated health center or in the respondent's home. Results: The response rate was 62.0%, with response rate varying according to educational attainment. Data from the first wave of data collection are available for researchers at the Irish Social Sciences Data Archive. Conclusion: The Irish Longitudinal Study on Ageing provides an opportunity to study the interactions between the health and social and economic circumstances of the older population in a nationally representative sample.